Process Clearance In & Clearance Out Millennium 806 Use the Application B-SIM by PT. Putra Samudera Inti in the Area Free Trade Zone Batam - Lamganda Uli Rosalina Ekatrikson Pasaribu; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
PT. Putra Samudera Inti Batam carried out the arrival and departure process for the Millennium 806 ship using the B-SIM application in the free trade zone area. Apart from that, the author also wants to know more about the process regarding the arrival and departure of the Millennium 806 ship using the B-SIM application. The method used in data collection is the field research method which consists of observation and interviews and the library research method. According to the process, the agent must ensure that the ship's next destination is the port in the Batam area, the agent completes the ship arrival request documents because before the ship arrives the agent must submit a ship arrival request or Ship General Statement (PUK), upload the documents into the B-SIM application, carry out verification to ensure that the data entered is correct until the fund hold is issued. After the activity is completed, the agent realizes the invoice in full to pay off the port service fees for the ship's departure. Agents always maintain good relations with other shipping companies and related agencies. With this good relationship, the process of managing the activities to be carried out by the ship can be maintained smoothly. Apart from that, the obstacle that occurs when requesting the ship's arrival and departure process is checking whether the note has been closed or whether the previous payment has not been paid. The arrival and departure process for ships using the B-SIM application must be carried out for every ship entering the Batam Free Trade Zone area and is carried out in accordance with applicable government regulations.